Lynk.id Digital Product Marketing Communication Strategy on the Instagram Account @tripplesixshot - Octavitto Praramadhan Alto Tamtomo; Farida Farida; Citra Rani Angga Riswari (Westscience Press, 2026)
This study is motivated by the increasing use of social media and the growing need for digital platform integration in digital product marketing, which has received limited attention from the perspective of Integrated Marketing Communication (IMC). The study aims to analyze the Lynk.id digital product marketing communication strategy implemented through the Instagram account @tripplesixshot and to explain the integration of cross-platform customer journeys. A qualitative approach employing the netnography method was adopted through one month of observations of Feed posts, Reels, Stories, captions, comments, Lynk.id links, WhatsApp, digital payment systems, and Google Drive. Data were analyzed using Kozinets' netnographic procedures, supported by triangulation to ensure the credibility of the findings. The results indicate that Instagram serves as the primary communication channel for building brand awareness, trust, and audience engagement through visual storytelling and portfolio presentation. Lynk.id functions as the central integration hub connecting Instagram, WhatsApp, digital payment systems, and Google Drive, making communication and transaction processes more efficient. Two-way communication enhances audience engagement, customer loyalty, and electronic word-of-mouth within the automotive community. The integrated digital customer journey creates a consistent customer experience while improving communication effectiveness, operational efficiency, and purchase conversion opportunities. The study concludes that the implementation of Integrated Marketing Communication and Digital Integrated Marketing Communication establishes an integrated digital marketing ecosystem for creative businesses. It is recommended that creative entrepreneurs optimize cross-platform integration, maintain content consistency, and strengthen audience interaction to enhance customer experience and digital marketing performance.